PENYUSUNAN DAN UJI COBA PROGRAM INTERPROFESSIONAL EDUCATION (IPE) DARING PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS X: SEBUAH STUDI DENGAN METODE CAMPURAN - Suryanti, Suryanti; Diantha, Soemantri; Sandra, Widaty; Hamzah, Hamzah (LPPM Universitas Bina Bangsa, 2023)
InterProfessional education (IPE) is a strategy used to prepare interprofessional collaboration teams in the future. However, with the various restrictions on social interaction during the COVID-19 pandemic, it encourages innovation in learning methods. Therefore, this study aims to design an online interprofessional learning module at the Faculty of Medicine of X University (FK X) as a strategy to prepare collaboration teams in the future. This study uses a mixed-method approach to obtain the data needed. A qualitative approach is used to obtain an overview of stakeholders' needs for online IPE learning design. The respondents consisted of study program leaders, lecturers and students of several study programs at the Faculty of Medicine, University X (FK X). Data collection was carried out with structured interviews and focus group discussions (FGDs). The data is recorded and made verbatim, then coding is carried out and arranged into themes and sub-themes. Evaluation of the online IPE teaching design was carried out by measuring students' perceptions of interprofessional education before and after taking the module using the IEPS (Interdisciplinary Education Perception Scale) questionnaire. The first stage of qualitative research (structured interviews and FGDs) on the leadership element, 2 lecturers, and 5 students of each study program resulted in as many as 14 themes and 47 sub-themes which were described into module learning outcomes, study topics, learning activities, and characteristics of online IPE module students. The module evaluation was carried out by testing the differences in perceptions of 252 students towards pre- and post-module interprofessional education. Wilcoxon's bivariate test results showed a significant difference in perception scores for post-module inteprofessional education compared to premodule( p=0.00). There is a positive difference, namely the number of post-module scores that are greater than the pre-module score of 141 people. The increase in perception scores can also be seen from the results of the bivariate analysis of the Medicine, Nursing, Midwifery, and Psychology Study Programs. This research shows that the implementation of the FK X online IPE module has succeeded in increasing students' perceptions of competence and autonomy, the perceived need to cooperate, and perceptions of interprofessional cooperation. This breakthrough is an alternative solution that can be considered for interprofessional learning during a pandemic